Arbiters of effectiveness and efficiency: the frames and strategies of management consulting firms in US higher education reform. Issue 5 (3rd September 2017) - McClure, Kevin R.
ABSTRACT: A growing number of public colleges and universities in the United States have hired management consulting firms to help develop strategies aimed at increasing institutional effectiveness and efficiency. The purpose of this paper is to explore the frames and strategies of consultants in US public higher education reform efforts. Drawing upon a range of documentary evidence, the paper examines four consulting firms (Accenture, Bain & Company, Deloitte and McKinsey & Company) and their perspectives on higher education reform. The paper analyses the consultative process with two public universities and two state higher education systems to determine possible avenues by which consultants exert influence. Through reference to theory on academic capitalism and new institutionalism, the paper reveals the ways in which consultants circulate crisis narratives and diffuse private sector management ideas among public colleges and universities that are seeking both financial solvency and legitimacy.